Critical Thinking in Various Risk Assessment Issues to Benefit Malaysian Small and Medium Sized Enterprises (SMEs) - Guo, Ryan Yang; Lee, Su Yan (2009)
Information is the priceless assets in all size of businesses. This is widely accepted nowadays. In order to protect information away from the threats, it has becomes a very challenging job with the needs of comprehensive resources, it can be extremely difficult for Small and Medium Sized Enterprises (SMEs), not only because of they have lack of resources, they may have no ideas about the prioritized tasks. Risk Assessment however is the best way to make SMEs to have a clearer vision on where are they standing and how far they need to go. In this paper, we present some of our findings from a printed survey to illustrate the problems in the current practice on information security within Malaysian SMEs. Some questions in this survey are focused on identifying the problems on risk assessment faced by the Malaysian SMEs. In addition, we discuss the some advices in assisting SMEs to carry out risk assessment in a more effective and efficiency way.